The Implementation of Personal Selling Impact To Consumer Purchasing Decision (Eyeglasses Product) At Krida Optical Bandung - Oman Sukriman; Dadang Rohandi (JURISMA : Jurnal Riset Bisnis & Manajemen, 2015)
Personal selling is face to face interaction with one or more prospective purchase for the purpose of making presentations, answering question, and procuring ordersales. Meanwhile, consumer purchasing decisions as an individual process of selecting, organizing, and interpreting the input information to create a meaningful picture of the world. The aim of this research is to analyzing implementation of personal selling an eyeglasses impact to consumer purchasing decision at Krida Optical Bandung.Research developed by using and survey method. This research also using descriptive and verifikatif methods. Population 600 consumer, and the technique of sample this reseach which using a random sampling with the result that for obtainabl 86 consumer as sample. Technique in collecting data by use of interview, observation, questioners and documentation. The analyze method by use of a correlation of rank spearman, and coefficient of determination, as well as test of t with by use of help SPSS 12.0 for windows.The result of this reseach represent that there are pursuant to comment of respondents of implementation personal selling is enough, same as consume purchasing behaviour is enought. The result of analysis this reseach represent that there are implementation personal selling impacted to consumer purchasing behaviour level relation indicate showing level enough with contribution the impact as much as 26.21%, and the rest as much as 73.79% representing impact by another factors which not analyzed as a inisiator, influence, devider, buyer, user.Â Â